2020
DOI: 10.6004/jnccn.2020.7558
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Immunotherapy–Based Systemic Treatment in MMR-Deficient or MSI-High Rectal Cancer: Case Series

Abstract: Treatment options for locally advanced rectal cancer have continued to consist largely of chemotherapy, chemoradiation, and/or surgical resection. For patients who are unable to undergo these therapeutic modalities or who do not to experience a response to them, treatment options are limited. We report 3 cases of mismatch repair–deficient (dMMR) locally advanced adenocarcinoma of the rectum that showed significant response with neoadjuvant immunotherapy–based systemic treatment. The first patient was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 16 publications
2
28
1
Order By: Relevance
“…Two of the studies did not present data on the MMR gene test analyses nor the MMR variant identified in the patients, and it remains uncertain how Lynch syndrome was diagnosed in these individuals. 28 , 29 The cases were identified in USA (N=13), Canada (N=3), China (N=3), Japan (N=2), France (N=1), Chile (N=1), UK (N=1), Brazil (N=1), and Australia (N=1). The responses were evaluated using the RECIST criteria (N=13), pathologic complete response with no viable tumor cells after surgery (N=2), tumor decrease with unknown percentage of decrease (N=7), clinical response with proceeded treatment due to no or little tumor progression (N=2), and as a decrease in prostate specific antigen (PSA) (N=2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of the studies did not present data on the MMR gene test analyses nor the MMR variant identified in the patients, and it remains uncertain how Lynch syndrome was diagnosed in these individuals. 28 , 29 The cases were identified in USA (N=13), Canada (N=3), China (N=3), Japan (N=2), France (N=1), Chile (N=1), UK (N=1), Brazil (N=1), and Australia (N=1). The responses were evaluated using the RECIST criteria (N=13), pathologic complete response with no viable tumor cells after surgery (N=2), tumor decrease with unknown percentage of decrease (N=7), clinical response with proceeded treatment due to no or little tumor progression (N=2), and as a decrease in prostate specific antigen (PSA) (N=2).…”
Section: Resultsmentioning
confidence: 99%
“…Since some of the cohort studies included few variants of unknown significance (VUS) as causative for Lynch syndrome 25 or included Lynch syndrome families based on individuals with dMMR/MSI tumors in families with a cancer history, 8 , 21 we chose to include two case studies with VUS 26 , 27 and two case studies with clinical Lynch syndrome diagnostics, but with unknown germline MMR gene variant. 28 , 29 Lynch syndrome individuals with biallelic MMR variants (also referred to as constitutional MMR deficiency (CMMR-D) syndrome) were also included in this study, since these tumors show the same molecular phenotype as monoallelic Lynch syndrome tumors (N=1). There were no selection criteria regarding tumor type and no restrictions in period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a case series of 3 patients with rectal cancer that was just reported this year. 1 Here we not only report a case of an advanced rectal cancer, but also a case of an advanced esophageal cancer who have achieved dramatic responses with no evidence of disease on repeated sampling. It is rare for surgery or radiation to be deferred in these situations.…”
mentioning
confidence: 88%
“…The 5-year survival prognosis is highly dependent on the tumor stage of CRC: over 90% survival for stage I CRC and nearly 10% survival for stage IV CRC ( 2 ). CRC treatments consist mainly of surgery combined with adjuvant chemotherapy and neoadjuvant radiotherapy ( 3 ). However, these therapies have not been proven to effectively cure CRC with many side effects.…”
Section: Introductionmentioning
confidence: 99%